Non-emulsion copolymerization in obtaining silicone-acrylic surfactant - Рубан, Олеся Владимировна; Киселёва-Логинова, Екатерина Валерьевна; Попов, Евгений Вадимович (Eastern-European Journal of Enterprise Technologies, 2014)
The experiment-based paper presents non-emulsion hybride copolymerization of acrylic acid and polydimethylsiloxane in making the most pure silicone acrylic polymeric surfactant. We have determined optimal conditions for the synthesis. The study of copolymerization kinetics by means of identifying the acid number has determined the best reasonable time and temperature for the reaction—2 hours and 120 respectively, since after 2 hours the acid conversion makes up 78%, whereas polymer yield is 66%. The synthesized silicone acrylic polymeric surfactant is a viscous transparent liquid that has no pungent smell and dissolves in organic solvents. We have identified and characterized the properties—molecular mass, viscosity and surface tension—of the obtained silicone acrylic polymer. The polymeric surfactant can be used as surface modifier in lacquer and paint products.